Comparative analysis of the meteorological conditions and tropospherical circulation at Akademik Vernadsky in 1999 - V. Ye. Timofeyev (Ukrainian Antarctic Journal, 2003)
The comparative analysis of meteorological regime and synoptic circulation at the Vernadsky station in 1999 and preceding years is presented. Annual averages of the air temperature of most winter months exceed its multi-years values by 2-5°C but some tendency to stabilization of its growth during last decade is noticed. Synoptic situations that lead to anomalous meteorological regime mostly in the atmospheric pressure and air temperature fields have been analyzed. Provisional types of synoptic processes are given. The main trajectories of the cyclones are western and north-western and development of the anticyclones almost completely depends on subtropic maximum intensification. The role of blocking wedge in the formation of the winter cold spell in 1999 is shown. Typical periods of settled weather at Vernadsky are found which can be taken into account when planning the outdoor season jobs at the base. Last years results of sea-ice observation are juxtaposed with those observed in the first decades of the base operating. The easier ice situation for the last decade is observed that is in accordance with the positive trend of annual average air temperatures through all the time of the base operation.